2019
DOI: 10.1021/acsaem.9b00867
|View full text |Cite
|
Sign up to set email alerts
|

Copper–Carbon: An Efficient Catalyst for Oxygen Reduction

Abstract: A simple and efficient method was developed to prepare a copper−carbon (Cu−C) catalyst with high oxygen reduction reaction (ORR) activity via direct pyrolysis of a mixture of metal salts (Cu(NO 3 ) 2 •3H 2 O and Zn(CH 3 COO) 2 ) and 1,3,5-benzenetricarbocylic acid at 1010 °C under a N 2 stream. It is found that the Cu−C catalyst exhibits superior catalytic activity toward ORR with a half-wave potential of 0.81 V and a four-electron transfer pathway in 0.1 M KOH electrolyte. Generally, it is known that N plays … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…Although precious metal-related catalysts, such as Pt, Pd, Ag-MnOx, or IrO 2 , are active OER/ORR catalysts, their large-scale application is hindered by their high cost and scarcity. , The catalysts can enhance the power density and modify reaction pathways and product structures. Reports show that copper-based catalyst derived from Cu-MOF precursor exhibited boosted ORR activity comparable to commercial Pt/C . There are a number of papers reporting the super effectiveness and possible mechanism of using copper catalysts for oxygen reduction or evolution reactions. …”
mentioning
confidence: 99%
“…Although precious metal-related catalysts, such as Pt, Pd, Ag-MnOx, or IrO 2 , are active OER/ORR catalysts, their large-scale application is hindered by their high cost and scarcity. , The catalysts can enhance the power density and modify reaction pathways and product structures. Reports show that copper-based catalyst derived from Cu-MOF precursor exhibited boosted ORR activity comparable to commercial Pt/C . There are a number of papers reporting the super effectiveness and possible mechanism of using copper catalysts for oxygen reduction or evolution reactions. …”
mentioning
confidence: 99%
“…[ 40 ] Natural abundance, wide range of oxidation states, and reliable and cost‐effective properties of copper [ 41 ] are fundamental reasons to justify its widespread application. Moreover, high capacity to accomplish a wide range of reactions like oxidation, [ 42 ] reduction, [ 43 ] and C–H activation [ 44 ] led to its loading on carbon‐based materials with the aim to improve its activity and stability.…”
Section: Introductionmentioning
confidence: 99%
“…[26,27] Our previous studies reported that both CuÀ NÀ C and CuÀ C catalysts exhibited good catalytic activities toward ORR. [28,29] Herein, Ni/Cu incorporated N-doped porous carbon materials (Ni 1-x Cu x -NÀ C, x = 0, 0.1, 0.3, 0.5, 0.7, and 1) were fabricated by a direct carbonization of the metal-organic complexes. The structure-related ORR properties were thoroughly presented and discussed.…”
Section: Introductionmentioning
confidence: 99%
“…Cu−N−C catalysts were reported to be excellent electrocatalysts for ORR attributed to the synergism of Cu and N dopants [26,27] . Our previous studies reported that both Cu−N−C and Cu−C catalysts exhibited good catalytic activities toward ORR [28,29] . Herein, Ni/Cu incorporated N‐doped porous carbon materials (Ni 1‐x Cu x ‐N−C, x=0, 0.1, 0.3, 0.5, 0.7, and 1) were fabricated by a direct carbonization of the metal‐organic complexes.…”
Section: Introductionmentioning
confidence: 99%